CGIAR System Transformation Initiatives join forces at the intersection of gender and climate for inclusive and resilient agrifood systems - Kyle, Jordan; Awinoh, Martha (CGIAR Initiative on Gender Equality, 2023)
On November 7, CGIAR Gender Equality Research Initiative, HER+, hosted a webinar convening researchers from across Initiatives in the CGIAR Systems Transformation Action Area CGIAR working at the intersection of gender and climate change. The webinar, aimed to facilitate the sharing of research findings and gave participants a chance to explore synergies and potential collaboration avenues, creating an environment for advancing research and actions at the intersection of gender equality and climate resilience in the context of agrifood systems.